Wearing Compression Tights on the Thigh during Prolonged Running Attenuated Exercise-Induced Increase in Muscle Damage Marker in Blood - Mizuno, Sahiro; Arai, Mari; Todoko, Fumihiko; Yamada, Eri; Goto, Kazushige (Frontiers in Physiology, 2017)
PURPOSE: To examine the effects of wearing a lower-body compression garment with different body coverage areas during prolonged running on exercise performance and muscle damage. METHODS: Thirty male subjects were randomly assigned to one of three groups: 1) wearing a compression tights with 15 mmHg to thigh [n = 10, CT group], 2) wearing a compression socks with 15 mmHg to calf [n = 10, CS group], and 3) wearing a lower-body garment with < 5 mmHg to thigh and calf [n = 10, CON group]. The exercise consisted of 120 min of uphill running at 55% of VO2max. Heart rate (HR), rate of perceived exertion (RPE), and running economy (evaluated by VO2) were monitored during exercise every 10 min. Changes in maximum voluntary contraction (MVC) of knee extension and plantar flexion, height of counter movement jump (CMJ) and drop jump (DJ), and scores of subjective feelings of muscle soreness and fatigue were evaluated before exercise, and 60 min and 180 min after exercise. Blood samples were collected to determine blood glucose, lactate, serum free fatty acid, myoglobin (Mb), high-sensitivity C-reactive protein, and plasma interleukin-6 concentrations before exercise (after 20 min of rest), at 60 min of exercise, immediately after exercise, and 60 min and 180 min after exercise. RESULTS: Changes in HR, RPE, and running economy during exercise did not differ significantly among the three groups. MVC of knee extension and plantar flexion, and DJ decreased significantly following exercise, with no difference among groups. The serum Mb concentration increased significantly with exercise in all groups, whereas the area under the curve for Mb concentration during 180 min post-exercise was significantly lower in the CT group (13,833 ± 1,397 pg/mL・180 min) than in the CON group (24,343 ± 3,370 pg/mL・180 min, P = 0.03). CONCLUSION: Wearing compression garment on the thigh significantly attenuated the increase in serum Mb concentration after exercise, suggesting that exercise-induced muscle damage was attenuated.